American History : A Survey - Brinkley, Alan (Boston McGraw-Hill, 2003)
Highly-respected for its impeccable scholarship and elegant writing style, American History: A Survey provides students and instructors with a comprehensive account of the American past in which no single approach or theme predominates. From its first edition, this text has included a scrupulous account of American political and diplomatic history. Today, however, the book explores areas of history such as social, cultural, urban, racial and ethnic history, more history of the West and South, environmental history, and the history of women and gender. In addition, American history has not evolved in a vacuum, but as part of a larger global world. The eleventh edition of this text places American history into that global context, making connections for students who live in an ever-expanding world themselves.
Include Index,Appendix and Colored Illustrations.
This book provides a balanced picture of the American past that connects the newer histories of society and culture that have emerged in the last several decades with the more traditional stories of politics, diplomacy, and great public events. American History: A Survey, eleventh edition, is accompanied by a comprehensive, well-integrated collection of print and electronic resources for both students and instructors.
Keywords: United States -- United States -- History -- Study and Teaching (Secondary)